2007
DOI: 10.1088/0957-0233/18/3/020
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure Diesel spray temperature measurements using two-colour laser-induced fluorescence

Abstract: This paper presents a new implementation of an optical technique which aims to measure the temporal and spatial evolution of the liquid temperature of a high injection pressure Diesel spray. Measurements are performed using the two-colour laser-induced fluorescence technique in which a temperature-sensitive fluorescent tracer is added to the fuel (ISO 4113 normafluid in the present case) and all the parameters except the temperature (e.g. tracer concentration, incident laser excitation, droplet number density)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 10 publications
0
37
0
Order By: Relevance
“…Temperature measurements in sprays: Several studies have more specifically addressed the implementation of the 2cLIF technique in sprays (Bruchhausen et al 2006;Depredurand et al 2011;Labergue et al 2010Labergue et al , 2012aWolff et al 2007). These studies describe how the 2cLIF technique, initially used and validated in the case of single calibrated droplets, should be modified for reliable measurements in sprays.…”
Section: Two-color Single-dye Laser-induced Fluorescence Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature measurements in sprays: Several studies have more specifically addressed the implementation of the 2cLIF technique in sprays (Bruchhausen et al 2006;Depredurand et al 2011;Labergue et al 2010Labergue et al , 2012aWolff et al 2007). These studies describe how the 2cLIF technique, initially used and validated in the case of single calibrated droplets, should be modified for reliable measurements in sprays.…”
Section: Two-color Single-dye Laser-induced Fluorescence Methodsmentioning
confidence: 99%
“…Depredurand et al (2011) showed that the size effect is drastically reduced when the dye concentration is increased. A high concentration in dye was also used by Wolff et al (2007) to perform measurements in high-pressure diesel sprays. However, in this work, high concentrations in dye were initially a mean of suppressing MDRs clearly visible both in the red and blue edges of the emission spectrum from droplets seeded with pyrromethene 597-C8.…”
Section: Two-color Single-dye Laser-induced Fluorescence Methodsmentioning
confidence: 99%
“…Both intensity images are affected by multiply scattered light, detected as "noisy" fluorescence on the inside of the hollow-cone. Multiply scattered light is a common phenomenon of hollowcone sprays and can only be suppressed by applying SLIPI 12 . The ratio of both intensity images is affected by multiply scattered light as well.…”
Section: Development Steps Of Pulsed 2d-2clif With Mdr-enhanced Energmentioning
confidence: 99%
“…MDRs occur regardless of the presence of any fluorescent dye. If a fluorescent dye is present, its emission spectrum is changed by the MDRs and reliable 2cLIF thermometry is prevented [2,12,13]. The term MDR describes light being trapped inside a droplet due to almost total internal reflection at the droplet's inner surface and going into resonances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation